Effect of acute hyperglycemia on left ventricular contractile function in diabetic patients with and without heart failure: two randomized cross-over studies. - Roni Nielsen; Helene Nørrelund; Ulla Kampmann; Hans Erik Bøtker; Niels Møller; Henrik Wiggers (PLoS ONE)
Background It is unknown whether changes in circulating glucose levels due to short-term insulin discontinuation affect left ventricular contractile function in type 2 diabetic patients with (T2D-HF) and without (T2D-nonHF) heart failure. Materials and methods In two randomized cross-over-designed trials, 18 insulin-treated type 2 diabetic patients with (Ejection Fraction (EF) 36 ± 6%, n = 10) (trial 2) and without systolic heart failure (EF 60 ± 3%, n = 8) (trial 1) were subjected to hyper- and normoglycemia for 9-12 hours on two different occasions. Advanced echocardiography, bicycle exercise tests and 6-minute hall walk distance were applied. Results Plasma glucose levels differed between study arms (6.5 ± 0.8 mM vs 14.1 ± 2.6 mM (T2D-HF), 5.8 ± 0.4 mM vs 9.9 ± 2.1 mM (T2D-nonHF), p<0.001). Hyperglycemia was associated with an increase in several parameters: maximal global systolic tissue velocity (Vmax) (p<0.001), maximal mitral annulus velocity (S'max) (p<0.001), strain rate (p = 0.02) and strain (p = 0.05). Indices of increased myocardial systolic contractile function were significant in both T2D-HF (Vmax: 14%, p = 0.02; S'max: 10%, p = 0.04), T2D-nonHF (Vmax: 12%, p<0.01; S'max: 9%, p<0.001) and in post exercise S'max (7%, p = 0.049) during hyperglycemia as opposed to normoglycemia. LVEF did not differ between normo- and hyperglycemia (p = 0.17), and neither did peak exercise capacity nor catecholamine levels. Type 2 diabetic heart failure patients' 6-minute hall walk distance improved by 7% (p = 0.02) during hyperglycemia as compared with normoglycemia. Conclusions Short-term hyperglycemia by insulin discontinuation is associated with an increase in myocardial systolic contractile function in type 2 diabetic patients with and without heart failure and with a slightly prolonged walking distance in type 2 diabetic heart failure patients. (Clinicaltrials.gov identifier NCT00653510).